The evolution of passenger transport in uzbekistan and its impact on economic growth - Naubetova, Ziyada (GREEN ECONOMY AND DEVELOPMENT, 2025)
This study uses a longitudinal approach to analyze Uzbekistan's passenger transport patterns from 2013 to 2023 and evaluate the economic implications. Road and metro dominate, with metro exhibiting the largest increase, suggesting urbanization, according to an analysis of road, air, rail, trolleybus, and tram. Trams and trolleybuses remained minor, while rail and air had moderate growth. Issues with sustainability, connectivity, and equal access still exist despite the COVID recovery. For a sustainable transportation system, recommendations include updating public transportation, emphasizing green mobility, improving multimodal connections, and enlisting the private sector more